VOLATILITAS ARUS KAS, TINGKAT UTANG, BOOK TAX DIFFERENCES DAN DAMPAKNYA TERHADAP PERSISTENSI LABA - Anthony Holly (Magister Akuntansi, Universitas Atma Jaya Makassar, 2019)
The purpose of this research is to investigate cash flow volatile, debt level, book tax differences and its impact to earning persistence. This research using companies listed in Indonesia Stock Exchange as sample. Sample selected by purposive sampling method. Data type used in this study is quantitative data and analyzed using multiple regression analysis to analysis dependent variable, earning persistence, and independent variable, cash flow volatile, debt level and book tax differences. The result of the research revealed cash flow volatile and debt level have negative and significant effect to earning persistence because higher volatile of cash flow and higher debt level, the earning resulted less persistence. Book tax differences has no effect to earning persistence. Investors see that the differences between earning reported as accounting income and taxable income as the common process resulted by the differences of the rule in recognition of income and expenses which has no effect in earning persistence.